Occupational Aspirations and Investments in Education: Experimental Evidence from Cambodia - Esther Gehrke; Friederike Lenel; Claudia Schupp (Center for Economic Studies and ifo Institute (CESifo), 2023)
Students in low-income contexts often lack guidance in their career decisions which can lead to a misallocation of educational investments. We report on a randomized field experiment conducted with 1715 students in rural Cambodia and show that a half-day workshop designed to support adolescents in developing occupational aspirations increased educational investments. We document substantial heterogeneity in treatment effects by baseline student performance. While the workshop increased schooling efforts of high-performing students, treated low-performing students reduced their educational investments. We develop a simple model that explains why an information intervention can affect educational aspirations and investments in opposing directions.
Keywords: C93; D83; D90; I21; O15; 330; aspirations; career guidance; education; field experiment